2018
DOI: 10.1186/s12978-018-0631-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adverse birth outcome and associated factors among women who delivered in Hawassa town governmental health institutions, south Ethiopia, in 2017

Abstract: BackgroundMost pregnancies are unplanned in Ethiopia. This is due to ignorance of the types and efficacy of each method of contraception they are associated with vast and unpredictable complications. Most of the time, these complications result in adverse birth outcomes. Information about prevalence of adverse birth outcome and it’s factors are relevant for designing, and initiating and intervening programs to decrease these undesirable out comes.ObjectiveTo assess prevalence of adverse birth outcome and assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
75
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(112 citation statements)
references
References 23 publications
31
75
6
Order By: Relevance
“…In addition, findings also showed that those women who have at least one previous abortion were at greatest risk of giving LBW neonates as evidenced by a study done in Ethiopia [28], Denmark, and the USA [49,50] and a meta-analysis in Canada [17]. The report also in-line with the study by Bossley [51] showed that women who had an abortion in the first or second trimester had a 35% increased risk of a LBW baby and a 36% raised risk of a preterm baby in later pregnancies and Ethiopia [52] found that previous adverse pregnancy outcomes were associated with recent outcome. This can be explained by physical damage to the cervix caused by types of abortion, reduced tensile strength of the cervical plug, preterm birth subsequently causing LBW, and stress/depression for the previous occurrence of the event.…”
Section: Obstetrical Factorssupporting
confidence: 53%
“…In addition, findings also showed that those women who have at least one previous abortion were at greatest risk of giving LBW neonates as evidenced by a study done in Ethiopia [28], Denmark, and the USA [49,50] and a meta-analysis in Canada [17]. The report also in-line with the study by Bossley [51] showed that women who had an abortion in the first or second trimester had a 35% increased risk of a LBW baby and a 36% raised risk of a preterm baby in later pregnancies and Ethiopia [52] found that previous adverse pregnancy outcomes were associated with recent outcome. This can be explained by physical damage to the cervix caused by types of abortion, reduced tensile strength of the cervical plug, preterm birth subsequently causing LBW, and stress/depression for the previous occurrence of the event.…”
Section: Obstetrical Factorssupporting
confidence: 53%
“…In our nding women with a previous history of adverse birth outcomes were signi cantly associated with adverse birth outcomes. This is in line with the report from other studies from china, Tanzania and Ethiopia (16,17,21,22). This might be due to most bad obstetrics histories are recurrent and more likely to result in adverse birth outcome in subsequent pregnancies.…”
Section: Discussionsupporting
confidence: 91%
“…In this study the prevalence of preterm birth was 5%. This nding is consistent with that of Hawassa (3.6%) (16) and Butajira (6.4%)(18) but lower than that of Wollo (13.2%) (19) and Gondar (14.3%) (17). The difference may be due to variation in populations and study setting and quality of maternal healthcare service.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The stillbirth rate of 284 per 1000 births is unacceptably high. This is almost twice as high as findings from a general population in public health facilities in southern Ethiopia (n=183) and more than ten times higher than the average stillbirth rate (25 to 31 per 1000 births) in the general population in low-income settings of southern Africa and Asia [29,30].…”
Section: Viewpoints Papersmentioning
confidence: 52%